2014
DOI: 10.1007/s40618-014-0210-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D levels and peripheral neuropathy in patients with type 2 diabetes: a systematic review and meta-analysis

Abstract: Vitamin D is involved in the development of DPN in type 2 diabetic patients, and vitamin D deficiency is very likely to be associated with DPN in type 2 diabetic patients. Further studies are needed to validate the association between vitamin D deficiency and DPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 29 publications
5
37
1
7
Order By: Relevance
“…Furthermore, a meta-analysis in type 2 diabetes (n ¼ 1484) confirmed a significant correlation between serum vitamin D 3 levels and the risk for DPN. 187 An open-label, prospective study conducted in Pakistan found a single IM-administered dose of 600,000 IU of vitamin D 3 provided significant pain relief in painful DPN. 188 More data are required before the role of vitamin D supplementation in painful DPN is established.…”
Section: Intravenous Lidocainementioning
confidence: 99%
“…Furthermore, a meta-analysis in type 2 diabetes (n ¼ 1484) confirmed a significant correlation between serum vitamin D 3 levels and the risk for DPN. 187 An open-label, prospective study conducted in Pakistan found a single IM-administered dose of 600,000 IU of vitamin D 3 provided significant pain relief in painful DPN. 188 More data are required before the role of vitamin D supplementation in painful DPN is established.…”
Section: Intravenous Lidocainementioning
confidence: 99%
“…Although previous studies have evaluated only DN-related pain, our study is the first to evaluate both neuropathic pain and balance. [12][13][14][15]21 Our results showed a significant improvement in the total DN4 questionnaire scores that indicates the presence of neuropathic pain and Berg balance test scores that determines balance after vitamin D replacement therapy. Various considerations are available regarding the dose, administration route, and duration of vitamin D replacement therapy.…”
Section: Discussionmentioning
confidence: 56%
“…Electrophysiological data suggest that the time needed to document the changes in Berg balance test scores is >8 weeks, which corresponds to axonal regeneration time. 21 In the present study, the follow-up examinations were performed after 12 weeks, which allowed for the completion of axonal regeneration. This may explain the discrepancy observed between the results of the present study and those of some previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, taking into account that the inclusion criteria and (Pilz et al, 2011). Finally, vitamin D deficiency could contribute to ED occurrence as a consequence of neuropathy, especially given the fact that erection is a neuro-vascular event and vitamin D deficiency is likely to be associated with neuropathy (Lv et al, 2015). Finally, vitamin D deficiency could contribute to ED occurrence as a consequence of neuropathy, especially given the fact that erection is a neuro-vascular event and vitamin D deficiency is likely to be associated with neuropathy (Lv et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, because not all included seven studies for the meta-analysis evaluated the testosterone levels and excluded the cases with the lower reference range testosterone levels, we were unable to give a definite conclusion that ED was resulted from testosterone deficiency solely in this case. Finally, vitamin D deficiency could contribute to ED occurrence as a consequence of neuropathy, especially given the fact that erection is a neuro-vascular event and vitamin D deficiency is likely to be associated with neuropathy (Lv et al, 2015).…”
Section: Discussionmentioning
confidence: 99%